ANALISIS PERAN SEKOLAH MINGGGU DALAM PENGEMBANGAN ASPEK PERKEMBANGAN AGAMA DAN MORAL ANAK USIA DINI - nona sifra t.talan zakarias talan; Lydia Ersta Kusumaningtiayas; Paulus Widjanarko (Widya Wacana: Jurnal Ilmiah, 2022)
This research was conducted in December - January on Sunday school teachers at the GUPDI church pasar legi Surakarta. This type of research was a descriptive qualitative research. The research subjects were GUPDI Sunday school teacher pasar legi Surakarta.Data collection techniques were through observation,intervie interview,and documentation.Observation was used to observe the role of sunday school teachers in accompanying and educating children. Interviews were conducted to obtain information needed by researchers. the documentation children out is to collect data and media about Sunday school teachers in educating children in the GUPDI church pasar legi Surakarta. The techninque of checking the validity of qualitative data was through technical triangulation. The method of analysis in this study was through data reduction, data presentation, data collection and conclusions. Based on the results of the study, it could be shown that 1) Sunday school teachers at the GUPDI church pasar legi Surakarta had an important role in assisting the religious and moral development of aerly childhood, 2) Sunday school teachers carried out their duties in providing services and instilling religious and moral values to children in a holistic manner. responsible and loving, 3) Sunday school teacher's strategy in educating and guiding children was to give advice and motivation. The cooperation of teachers and perents could develop children's personality to be better.